2014
DOI: 10.11648/j.ijema.20140206.13
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Selected Heavy Metals in Soil, Tomatoes and Selected Vegetables from Lushoto District-Tanzania

Abstract: Abstract:This study involved the determination of heavy metals of Cd, Cr, Cu, Pb and Zn in cauliflower (Brassica oleracea L.var botrytis L.), carrot root (Daucus carota L.), tomato fruit (Lycopersicum esculentum Mill.), onion bulb (Allium cepa L.) and leafy cabbage (Brassica oleracea L. var capitata L.) and the respective soils from Lushoto District, Tanzania. Samples were collected from eight growing sites. The accumulated heavy metals were quantified and the levels compared to the FAO/WHO CODEX-STAN 179:2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Concentration of iron in vegetables Concentration of iron in fruits & peels of fruits samplesLead: It is not essential heavy metal and is highly toxic for microorganisms, plants and animals, its use in very small quantity can cause environmental and health problems that affect the multiple body systems, Pb can enter the body through breathing in air contaminated with Pb as it gets into the lungs transported into the other parts of the body and is deposited into the bones. It affects the central nervous system, I.Q of children and behaviour, Alteration in sperms decrease the fertility in men and increase the chance of miscarriage and defects in birth in women[18].The concentration of lead in the fruit samples such as peach was observed higher than all the vegetable samples whereas other fruit samples showed no any important difference. The fruit samples such as water melon and peach indicated higher concentration of lead than the peels of all fruit samples The concentration of Pb crossed the safe values in all samples of fruits and vegetables except lady finger and cauliflower in which concentration of Pb lies in safe limits.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Concentration of iron in vegetables Concentration of iron in fruits & peels of fruits samplesLead: It is not essential heavy metal and is highly toxic for microorganisms, plants and animals, its use in very small quantity can cause environmental and health problems that affect the multiple body systems, Pb can enter the body through breathing in air contaminated with Pb as it gets into the lungs transported into the other parts of the body and is deposited into the bones. It affects the central nervous system, I.Q of children and behaviour, Alteration in sperms decrease the fertility in men and increase the chance of miscarriage and defects in birth in women[18].The concentration of lead in the fruit samples such as peach was observed higher than all the vegetable samples whereas other fruit samples showed no any important difference. The fruit samples such as water melon and peach indicated higher concentration of lead than the peels of all fruit samples The concentration of Pb crossed the safe values in all samples of fruits and vegetables except lady finger and cauliflower in which concentration of Pb lies in safe limits.…”
mentioning
confidence: 93%
“…These are rich sources of vitamins, Fiber, minerals and also have importance as anti-oxidative effects for proper growth, body development, and maintenance of overall health [1]. Other than water and soil, foods are also contaminated with heavy metals due to the use of chemicals sprays, preservatives, industrialization, mining activities, fertilizers and use of waste water [2]. Contamination of Heavy metal in fruits and vegetables is one of the most significant aspects of food quality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that fruits and leafy vegetables are vulnerable to heavy metal contamination from soil, wastewater and air pollution. The toxicity and consequent threat to human health by heavy metals such as cadmium, copper, lead, chromium, zinc, nickel, cobalt, arsenic and mercury are a function of concentration and bioaccumulation [6,7]. The implications associated with metal contamination are of great concern, particularly in agricultural production systems due to their increasing trends in human foods and environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…This fact necessitates for frequent determination of heavy metals in vegetables and soil for the safety of consumers. Fruits, vegetables and other foods are among pathways by which heavy metals enter the human tissues leading to deterioration of health [7]. Excessive amount of heavy metals in food cause a number of diseases, especially cardiovascular, renal, neurological, and bone diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…from soil, wastewater and air pollution [2,3] and as such serve as the pathways by which heavy metals enter the human tissues leading to deterioration of health [4]. Butea monosperma (family Fabaceae) commonly called Palash and "Flame of the forest" is reported in various ancient literatures to have medicinal potential.…”
mentioning
confidence: 99%